Solitary Large Intestinal Diverticulitis in Leatherback Turtles (Dermochelys coriacea). (July 2015) - Stacy, B. A.; Innis, C. J.; Daoust, P.-Y.; Wyneken, J.; Miller, M.; Harris, H.; James, M. C.; Christiansen, E. F.; Foley, A.
Leatherback sea turtles are globally distributed and endangered throughout their range. There are limited data available on disease in this species. Initial observations of solitary large intestinal diverticulitis in multiple leatherbacks led to a multi-institutional review of cases. Of 31 subadult and adult turtles for which complete records were available, all had a single exudate-filled diverticulum, as large as 9.0 cm in diameter, arising from the large intestine immediately distal to the ileocecal junction. All lesions were chronic and characterized by ongoing inflammation, numerous intralesional bacteria, marked attenuation of the muscularis, ulceration, and secondary mucosal changes. In three cases, Morganella morganii was isolated from lesions. Diverticulitis was unrelated to the cause of death in all cases, although risk of perforation and other complications are possible.